1969
DOI: 10.1111/j.1748-1716.1969.tb04553.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Reflex Activation of the Sympathetic Cholinergic Vasodilator Nerves in the Dog

Abstract: Sympathetic, cholinergic kasodilatation in skeletal muscle was induced as orienting and conditional reflex responses in conscious dogs. A sound stimulus elicited an orienting reflex accompanied by an atropine‐sensitive vasodilatation in the skeletal muscles of the hind limb. Further, a tachycardia and a slight blood pressure rise were noticed. The orienting reflex response disappeared gradually on repetition of the sound stimulus. The same cardiovascular events were obtained as conditional reflexes to both ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…(1964), as preparation for the defence reaction, and whether it may be compared with the behaviour we have studied. A muscle vasodilatation, presumed to be largely cholinergic because reduced by atropine, has been recently described by Bolme & Novotny (1969) in dogs during a conditioned response to painful stimulation. It is unknown, however, how far uncontrolled movement might have contributed to this vasodilatation, and is equally uncertain, even according to Bolme & Novotny, whether the vasodilatation is really related to the emotional background of the conditioned reflex.…”
Section: Discussionmentioning
confidence: 97%
“…(1964), as preparation for the defence reaction, and whether it may be compared with the behaviour we have studied. A muscle vasodilatation, presumed to be largely cholinergic because reduced by atropine, has been recently described by Bolme & Novotny (1969) in dogs during a conditioned response to painful stimulation. It is unknown, however, how far uncontrolled movement might have contributed to this vasodilatation, and is equally uncertain, even according to Bolme & Novotny, whether the vasodilatation is really related to the emotional background of the conditioned reflex.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, there are few behavioral situations that do not involve overt movement, and those that do not often involve the anticipation of or the preparation for movement. Since the cardiovascular exercise pattern can occur in anticipation of movement (26), it must be considered as a major potential contributor to the cardiovascular concomitants of many behavioral situations. Thus, we wish to recap very briefly the neurally mediated components of this response pattern.…”
Section: Reflex Behavioral Modelsmentioning
confidence: 99%
“…In a similar experiment, Abrahams et al (83) paired a tone with an electric shock to the foot pads of cats and demonstrated a conditioned vasodilation in the hind limb; however, neither its relationship to limb movement nor its atropine sensitivity was assessed. Dogs have also been shown to develop atropine-sensitive, conditioned blood flow increases in hind limb muscles during similar paradigms (26,84). The study of Bolme and Novotny (26) is of particular interest, since they were able to condition increased limb blood flow using either an electric shock or exercise as the unconditioned stimulus.…”
Section: Direct Reinforcement Of Cardiovascular Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which vasodilation to active skeletal muscles is maintained is poorly understood. It is well known that ␤-adrenergic receptors and muscarinic receptors are present in the arterial vasculature of skeletal muscle (4,11,13,25). There is some evidence suggesting that sympathetic ␤adrenergic (11,14,15,20) and sympathetic cholinergic (22) receptors may play a role in the increase in blood flow to exercising skeletal muscle.…”
mentioning
confidence: 99%